Using the theory of planned behavior to understand student intent to use tobacco in California universities - Agroia, Harit K.; Nelson, Anna (International Journal Of Community Medicine And Public Health, 2022)
Background: Most tobacco use, including addiction, starts between 18-26 years of age. To prevent this, the University of California (UC) and California State University (CSU) have implemented system-wide tobacco-free policies in recent years. The objective of this study was to investigate the association of the theory of planned behavior (TPB) constructs: attitude, subjective norms (SN), and perceived behavioral control (PBC) with intention to use tobacco among students in tobacco-free universities in California. Additional objectives were to understand whether these primary TPB constructs were influenced by various policy enforcement levels (i.e., communication and signage), and the availability of smoking cessation programs on campus. Methods: In this cross-sectional study conducted during March-May 2018, a survey was administered among students within select UC and CSU campuses. Students were recruited by cold-calling and emailing faculty to request assistance in disseminating an electronic survey to their students. Results: There was a total of 167 survey respondents (mean age=18-24 years). Results indicated that attitude (β=0.12, p<0.025), SN (β=0.18, p<0.001), and PBC (β=0.33, p<0.001) were significantly and positively associated with student intention. Results showed no significant differences between different enforcement levels and TPB constructs but did show significant positive differences in student attitude between campuses that offer smoking cessation programs and campuses that do not (t=2.55, f=6.50, p<0.001). Conclusions: Findings indicate tobacco-free policies positively influence shifts in student attitude and intention to use tobacco on California university campuses. Administrators are encouraged to tailor enforcement messages to increase compliance.